SCIENTIFIC AND EDUCATIONAL CENTERS: TO A NEW PARADIGM OF ENGINEERING EDUCATION - Andrey N. Morozov; Valeriy E. Karasik; Olga S. Erkovich (Высшее образование в России)
The article is devoted to the innovative system of the scientific and educational centers formed at Bauman Moscow state technical university, their contribution to training of graduates. It is shown that the system of the scientific and educational centers combining real production, scientific researches, business processes and modern educational technologies provides the necessary conditions and a special environment for training of specialists ready to participate in innovative development, and to shape the future of the Russian science and the industry.